Rotating speed and magnetic pole dependency assisted on copper deposition onto aluminum alloy substrate for bacterial eradication application - Basori, Basori; Ruliyanta; Ajiriyanto, Maman Kartaman; Kriswarini, Rosika; Hardiyanti, Heri; Rosyidan, Cahaya; Yudanto, Sigit Dwi; Situmorang, Evi Ulina Margaretha; Edbert, Daniel; Nanto, Dwi; Susetyo, Ferry Budhi (Communications in Science and Technology, 2025)
Copper (Cu) is widely used in many sectors, such as drinking water piping, heat exchangers, and medical equipment. The present research conducted an electrodeposition of Cu over an aluminum (Al) alloy substrate under the influence of various magnetic poles and rotating speeds. In the present study, a number of investigations, including deposition rate, current efficiency, coating thickness, surface morphology and phase, crystallographic orientation, antibacterial activity, electrochemical behavior, and hardness test were conducted. Increasing the rotation speed promoted to enhanced deposition rate and current efficiency for both magnetic poles influence. An increase in the deposition rate from 12.83 to 13.67 µm/h led to the increasing thickness, a change in surface morphology near the spheroidal, becoming a faceted structure. Presenting and rising in the rotation of a magnetic field led to a reduced surface roughness and crystallite size of Cu film for both magnetic poles influence. The Cu film made without spinning magnetic had a characteristic of highest bacterial inhibition zone around 2.50 ±0.56 cm². The CuRN50 sample had the lowest corrosion rate at around 0.055 mmpy, while the CuRS100 sample had the highest hardness value at approximately 80.72 HV for having the lowest crystallite size. Cu coated onto Al alloy could enhance its properties, such as being antimicrobial, being resistant against corrosion and having the hardness value.